Multiple sex chromosomes in the light of female meiotic drive in amniote vertebrates - Pokorná, Martina; Altmanová, Marie; Kratochvíl, Lukáš (Chromosome research, 2014)
It is notable that the occurrence of multiple sex chromosomes differs significantly between major lineages of amniote vertebrates. In this respect, birds are especially conspicuous, as multiple sex chromosomes have not been observed in this lineage so far. On the other hand, in mammals, multiple sex chromosomes have evolved many times independently. We hypothesize that this contrast can be related to the different involvement of sex-specific sex chromosomes in female meiosis subjected to the female meiotic drive under male versus female heterogamety. Essentially, the male-specific Y chromosome is not involved in female meiosis and is therefore sheltered against the effects of the female meiotic drive affecting the X chromosome and autosomes. Conversely, the Z and W sex chromosomes are both present in female meiosis. Nonrandom segregation of these sex chromosomes as a consequence of their rearrangements connected with the emergence of multiple sex chromosomes would result in a biased sex ratio, which should be penalized by selection. Therefore, the emergence of multiple sex chromosomes should be less constrained in the lineages with male rather than female heterogamety. Our broader phylogenetic comparison across amniotes supports this prediction. We suggest that our results are consistent with the widespread occurrence of female meiotic drive in amniotes.
Keywords: Reptiles; Sex Chromosomes; pohlavní chromozomy; Mammals; fylogeneze; Phylogeny; plazi; Meiosis; Models, Genetic; Inheritance Patterns; savci; meióza; ptáci; Birds; segregace chromozomů; typy dědičnosti; Animals; ženské pohlaví; zvířata; modely genetické; Chromosome Segregation; Female